PENGARUH MANAJEMEN SARANA KESEHATAN TERHADAP KEPUASAN PASIEN DI KLINIK PRATAMA PTPN VII KANTOR DIREKSI BANDAR LAMPUNG - Utomo, Muhammad Aditya; Purwadhi, Purwadhi; Hidayat, Dasrun (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
The purpose of conducting this research is to find out how much influence the management of health facilities has on patient satisfaction at PTPN VII Primary Clinic Office of the Board of Directors. The method used in this research is quantitative with the concept of cross-sectional study. The population in this research is all outpatient PTPN VII Pratama Clinic Office of the Board of Directors in 2022 and the sample collection method uses non-probability sampling with the accidental sampling method. So that a sample of 315 people was obtained. Based on the research results it is known that the P-Value simultaneously is 0.000. As for the partial infrastructure facilities (X1), location (X2), personnel (X3), and pharmacy (X4) variables have a P-Value 0.05, if the probability value is 0.05 so it can be concluded that infrastructure, location, personnel, and pharmacy influence simultaneously and partially on patient satisfaction (Y). Primary Clinics can maintain and improve aspects of manpower related to service and attitudes of officers such as through continuous briefings and outreach regarding a culture of responsive, mutual respect, and empathetic actions.